Design of Water Source Alternative Based on SWAT Model Simulation - Pandjaitan, Nora Herdiana; Afifi, Arif Yusron; Sapei, Asep (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Water shortage problem was often happened in many places in Indonesia. Water availability is very important not only for domestic needs, but also for other activities particularly for agricultural activities. To solve water shortage problem, this study aimed to design a water source alternative. The rain is a free water source and collecting rain in the small dam or reservoir is one of the effective rainwater harvesting technique that can increase water availability. This research was conducted  at Sekaran Village and the analysis had done using SWAT (Soil and Water Assessment Tools) model.  The planned rainfall and discharge were analysed by 5 years return period to calculate the water  potential for reservoir charging. The results of this study indicated that the location of the reservoir was planned in a forest area with a slope of 8-25%, on coordinates 111º38'11.39"E and 7º6'14.22"S and has a storage volume of 13737 m3. The reservoir has 4356 m2 surface area with a depth of 3 m. Based on the SWAT model simulation, the highest average discharge potential occured in February with a discharge of 0.312 m3/s and the lowest average discharge occured in October with a discharge of 0.044 m3/s. The total volume of potential annual water that can fill the reservoir is 61.166 m3/s per year based on a planned rainfall of 115.38 mm and a planned flood discharge of 2.54 m3/s with a return period of 5 years. The reservoir construction required a cost of  IDR 1,200,747,000. Keywords: Cost, Location, Rainwater Harvesting, Reservoir, SWAT